Influence of clinical characteristics on maternal DHA and other polyunsaturated fatty acid status in pregnancy: A systematic review. (March 2020) - Wilson, N.A.; Mantzioris, E.; Middleton, P.F.; Muhlhausler, B.S.
Highlights: Inconsistencies were observed in the findings of individual studies. Being overweight in pregnancy was associated with a higher maternal omega-3 status. Having gestational diabetes was associated with a higher maternal omega-3 status. First pregnancies were related to a higher maternal omega-3 status. Abstract: Introduction: Omega-3 DHA is important for the prevention of preterm birth, however there is limited knowledge of the determinants of omega-3 status during pregnancy. The primary objective of this systematic review was to synthesise data from existing studies assessing relationships between clinical factors and maternal DHA status. Materials and methods: The Medline, Embase, Amed, and CINAHL databases were searched for studies reporting measures of maternal omega-3 status and one or more clinical characteristics. Results: Eighteen studies were included in the final analyses. Factors associated with a higher BMI (overweight, higher gestational weight gain, gestational diabetes), or lower parity were each associated with higher omega-3 status in the majority of studies, with mixed findings for other comparisons. Discussion: Inconsistent findings between studies make it difficult to draw clear conclusions about the relationship between clinical factors and maternal omega-3 DHA status. However, maternal overweight and associated metabolic conditions may increase lipid metabolism.